Asynchronous transfer mode (mobility in wireless ATM) / Wan Mohd Zaid Wan Md Ali - Wan Md Ali, Wan Mohd Zaid (1998)
Mobility is importance features in future broadband technology it can make a new era of the information technology, h is also parallel to our vision is now invited people to know and love Information Technology. So Mobility is one of branches that can up bring up this technology to be more excited. In order to support such mobility for the broad band data especially (ATM), we need to look at in many aspect and entities on current data communication which reflect to support mobility. So this report is discussing and presenting report on wireeless ATM and its simulation by software Network n 5 Release 10.0. The mobility will be described basically on Handoff strategies, location management, and address migration. Mobile station is simulated to access network modelled to communicate from Mobile Station to Base station. ATM Switch which to transfer data (signalling messages) while to completion of hand over process. This to change or updating related entity to initiates hand over process in mobility environment. The ATM Switch is to make network can be connected to the backbone network .So h can be support more widely area. For simulation, network model will be presented where the sources are combination of three mobile stations. This simulation we assume that using wireless radio protocol as Collision. Here we are using collision protocol as radio link and First Come First Serve Protocol as ATM Link.